The feminised service sector: from micro to macro analysis. (1st April 2012) - Babs Grossman
Abstract : Research concerned with the relationship between gender and service work has typically relied on micro-level analyses, and privileged affective explanations of the feminised service sector. The resulting scholarship, which often uses the 'emotional labour' framework first introduced by Arlie Hochschild (1983), has come to dominate gender and service work literature in such a way that other potentially useful analytical frameworks have been left relatively unexplored. Recently, this approach has been critically engaged with by scholars in an attempt to expand and enrich understandings of the relationship between service occupations and gender on a global scale. In particular, new scholarship on gender and service work has called attention to the convergence of local understandings of gender within the new international division of labour. This emergent macro-level and transnational research represents an exciting new body of work that merits review and consideration.